The Effect of Microsoft PowerPoint Interactive Learning Media Application on Reading Comprehension Skills of 3rd Grade Elementary School Students for Indonesian Language Subjects - Maulidya Alvy Zahara; Abdul Rahman Jupri (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to analyze the effect of Microsoft PowerPoint interactive learning media application on the reading comprehension skills of 3rd grade elementary school students in Indonesian. This research method uses a quasi-experimental method with a Nonequivalent Control Group Design approach. The population of the study was the 3rd grade students of SDN Duren Sawit 07 Jakarta, totaling 60 students, divided into an experimental class and a control class. The research instrument used a pretest and posttest. While the data analysis technique used descriptive quantitative. The results of this study indicate that the average value of the experimental class at the pre-test = 56.67 has increased when the post-test is carried out = 82.00, while the results of the average value of the control class at the pre-test = 53, 00 experienced an increase when the post-test was carried out = 73.33. The results of the t-test in this study obtained tcount as much as 3.7582 at a significant level = 0.05 and degrees of freedom (dk) = 2.0032. Because the value of tcount>ttable which is 3.7582 > 2.003 so that it can be achieved H0 is rejected, meaning that there is a difference in the improvement of students' reading comprehension skills using the Microsoft PowerPoint interactive learning media application using only conventional media.